Projekty realizowane przez Sekcję Filologii Polskiej Katedry Slawistyki Uniwersytetu im. Palackiego w Ołomuńcu - Ivana Dobrotová; Michał Hanczakowski (Postscriptum Polonistyczne)
The article chronologically presents projects in which Polish Studies Section has participated since 2004. The projects are a part of activities that Polish Studies Section is involved in – and along with glottodidactics and research activities – it determines the character of Polish Studies in Olomouc.